2021
DOI: 10.1155/2021/9956256
|View full text |Cite
|
Sign up to set email alerts
|

Canine Gastrointestinal Nematodiases and Associated Risk Factors in Kigali City, Rwanda

Abstract: Canine nematodes pose a public health risk to humans and livestock; however, the prevalence of canine nematodiases in Rwanda is unknown. This study aimed at determining the prevalence of canine nematodiases and identifying the risk factors for such infections in Kigali, the capital city of Rwanda. A cross-sectional study involved 93 dogs selected across Kigali city. Faecal samples were collected from apparently healthy dogs, and nematode eggs were identified and quantified using the McMaster technique. Risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
0
8
2
Order By: Relevance
“…Such circumstances would predispose dog owners and farmers towards sourcing animal health information from their peers rather than veterinarians. The 61.6% of our respondents who acquired information on canine zoonotic helminths from colleagues and friends was higher than 48% found in Ethiopia (Kiflu et al., 2016). Again, 14.3% of those who sourced it from professionals, including veterinarians, was lower than 18.6% (Kiflu et al., 2016).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Such circumstances would predispose dog owners and farmers towards sourcing animal health information from their peers rather than veterinarians. The 61.6% of our respondents who acquired information on canine zoonotic helminths from colleagues and friends was higher than 48% found in Ethiopia (Kiflu et al., 2016). Again, 14.3% of those who sourced it from professionals, including veterinarians, was lower than 18.6% (Kiflu et al., 2016).…”
Section: Discussioncontrasting
confidence: 53%
“…In a study conducted in dogs in Rwanda, the prevalence of Ancylostoma spp was 32.3% while that of Toxocara canis and Ancylostoma spp coinfection represented 1.1% (Ntampaka et al, 2021). Another study conducted in school children in Rwanda reported the prevalence of hookworms of 1.9% (Kabatende et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, retrospective/ prospective studies conducted by Idika et al [24] in Nigeria, reported that dogs aged above 1 year had significantly (p < 0.05) higher prevalence (30.8%) than younger ones (20.9%). In Rwanda, the prevalence reported was 33.3% and dog's age, location, and feeding habits were associated risk factors [37]. The higher prevalence rate in young dogs, as seen in this study, might be due to their low innate immunity as well as transplacental and transmammary passage of larvae to them [38].…”
Section: Discussionmentioning
confidence: 74%
“…Factors can affect the proportion of helminthiasis in dogs such as age, sex, dog breed, food, environment, accuracy of sample examination, deworming, and geographic location (8). Knowing the epidemiological pattern of helminthiasis in different areas will provide a basic strategy for controlling helminthiasis.…”
Section: Introductionmentioning
confidence: 99%